2015
DOI: 10.1177/1759091415573985
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-Mediated Apoptosis in the Cochleae Contributes to the Early Onset of Hearing Loss in A/J Mice

Abstract: A/J and C57BL/6 J (B6) mice share a mutation in Cdh23 (ahl allele) and are characterized by age-related hearing loss. However, hearing loss occurs much earlier in A/J mice at about four weeks of age. Recent study has revealed that a mutation in citrate synthase (Cs) is one of the main contributors, but the mechanism is largely unknown. In the present study, we showed that A/J mice displayed more severe degeneration of hair cells, spiral ganglion neurons, and stria vascularis in the cochleae compared with B6 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…A previous study demonstrated that the expression of miR-29b was upregulated in AHL ( 5 ). In the present study, our results also confirmed that miR-29b was overexpressed in the cochleae of aging C57BL/6 mice, which is the most widely used mouse model for the study of aging and age-associated diseases ( 20 ). Of note, in our study, there was a significant decrease in the counts of hair cells and increased mitochondrial dysfunction in the cochleae of the aged C57BL/6 mice, which is in agreement with the findings of previous studies indicating that hair cell apoptosis is a key contributor to the development of AHL ( 4 , 21 ).…”
Section: Discussionsupporting
confidence: 87%
“…A previous study demonstrated that the expression of miR-29b was upregulated in AHL ( 5 ). In the present study, our results also confirmed that miR-29b was overexpressed in the cochleae of aging C57BL/6 mice, which is the most widely used mouse model for the study of aging and age-associated diseases ( 20 ). Of note, in our study, there was a significant decrease in the counts of hair cells and increased mitochondrial dysfunction in the cochleae of the aged C57BL/6 mice, which is in agreement with the findings of previous studies indicating that hair cell apoptosis is a key contributor to the development of AHL ( 4 , 21 ).…”
Section: Discussionsupporting
confidence: 87%
“…A number of specific and broad-spectrum peptide caspase inhibitors have been developed to elucidate the role of each specific caspase in cell death. Intraperitoneal injection of the pan-caspase-inhibitor z-VAD-FMK Z-VAD-FMK for eight weeks, starting at one week of age in DBA/2J and A/J mice, preserved hearing by more than 10 dB SPL in the ABR thresholds and significantly reduced OHC loss in the basal turns of the cochleae [120,121]. Even many caspase inhibitors (e.g., inhibitors of caspase-1, capses-2, caspase-6, and caspase-3) have been patented for their use in the treatments of neurodegenerative diseases, cardiovascular diseases, liver diseases, and cerebral stroke.…”
Section: Caspase Inhibitorsmentioning
confidence: 99%
“…Five mice in the mNGF group and five in the control group at the age of the 3rd, the 6th, and the 8th week were randomly chosen and anaesthetised with avertin (0.5 mg/g body mass). Sections of the inner ears were prepared, and SGN was observed and counted in accord with the methods described previously [ 7 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Histologically, the mice display progressive loss of hair cells and spiral ganglion neurons (SGNs) [ 6 ]. Recent studies show that caspase-mediated apoptosis is involved in the cochlear pathology [ 7 ]. These characteristics provide possibilities for drug intervention in the hearing impairment.…”
Section: Introductionmentioning
confidence: 99%